N,N-dimethylacetamide. A versatile solvent for pharmacological applications: anti-thyroid activity? - Martini, Nancy (2022)
N,N-dimethylacetamide is an industrialized solvent highly miscible with water, very useful in the pharma-cological and chemical areas. This well-known solvent possesses great therapeutic potential. Its use has been proven in the treatment of inflammatory-infective diseases together with its antibacterial effect and bone regeneration. In this short communication, its potential anti-thyroid activity is presented. The experiment is based on the interference with iodine incorporation into the tyrosine residues of thyroglobulin and avoids the biosynthesis of thyroid hormones. The interaction with iodine was evaluated by the Benesi-Hildebrand method. It was found that N,N-dimethylacetamide was able to form a charge-transfer complex with iodine with a KCTvalue higher than 100 M-1 which is a reference value for anti-thyroid activity. FTIR spectroscopy supports the formation of the charge-transfer complex which is assumed to occur via C=O--iodine interaction.